The White-Rot Basidiomycete Dichomitus squalens Shows Highly Specific Transcriptional Response to Lignocellulose-Related Aromatic Compounds - Kowalczyk, Joanna E.; Peng, Mao; Pawlowski, Megan; Lipzen, Anna; Ng, Vivian; Singan, Vasanth; Wang, Mei; Grigoriev, Igor V.; Mäkelä, Miia R. (Frontiers in Bioengineering and Biotechnology, 2019)
Lignocellulosic plant biomass is an important feedstock for bio-based economy. In particular, it is an abundant renewable source of aromatic compounds, which are present as part of lignin, as side-groups of xylan and pectin, and in other forms, such as tannins. As filamentous fungi are the main organisms that modify and degrade lignocellulose, they have developed a versatile metabolism to convert the aromatic compounds that are toxic at relatively low concentrations to less toxic ones. During this process, fungi form metabolites some of which represent high-value platform chemicals or important chemical building blocks, such as benzoic, vanillic and protocatechuic acid. Especially basidiomycete white-rot fungi with unique ability to degrade the recalcitrant lignin polymer are expected to perform highly efficient enzymatic conversions of aromatic compounds, thus having huge potential for biotechnological exploitation. However, the aromatic metabolism of basidiomycete fungi is poorly studied and knowledge on them is based on the combined results of studies in variety of species, leaving the overall picture in each organism unclear. Dichomitus squalens is an efficiently wood-degrading white-rot basidiomycete that produces a diverse set of extracellular enzymes targeted for lignocellulose degradation, including oxidative enzymes that act on lignin. Our recent study showed that several intra- and extracellular aromatic compounds were produced when D. squalens was cultivated on spruce wood, indicating also versatile aromatic metabolic abilities for this species. In order to provide the first molecular level systematic insight into the conversion of plant biomass derived aromatic compounds by basidiomycete fungi, we analyzed the transcriptomes of D. squalens when grown with ten different lignocellulose-related aromatic monomers. Significant differences for example with respect to the expression of lignocellulose degradation related genes, but also putative genes encoding transporters and catabolic pathway genes were observed between the cultivations supplemented with the different aromatic compounds. The results demonstrate that the transcriptional response of D. squalens is highly dependent on the specific aromatic compounds present suggesting that instead of a common regulatory system, fine-tuned regulation is needed for aromatic metabolism.